Comparing the effect of occupational stress on oil and gas industry workers in Nigeria with respect to age and gender. - FINIAN, Okechukwu Iwu; Achalu , E. O.; Patrick , C. (European Journal of Applied Sciences, 2021)
The petroleum industry in Nigeria has positively impacted the Nigerian economy. Sadly, the industry has also recorded high incident rates and has maintained the upward trend as reported by the Department of Petroleum Resource (DPR) in their 2015 publication of the petroleum industry health and safety performance score card. The report indicates that fatality in the oil and gas industry had risen by 244% between 2010 to 2015 and that the death toll reached 217 within the same period. The deaths were recorded from 298 incidents reported industry-wide within the five-year period and the reasons are not farfetched. The workers in the oil and gas industry have continually faced unfavorable work environments and conditions, lengthy working hours, achieving ambitious targets and deadlines, workplace competition and other workplace stress factors which led to fatigue, substance abuse to keep up with work, poor judgments and accidents as the eventual outcome. Previous studies have confirmed the risky nature of petroleum exploration and prevalence of stress elements faced by the industry workers while some other studies have established the relationship between occupational stressors and workplace incident in the oil and gas industry. This study therefore will focus on the comparison of oil and gas industry workers response to the effect of stress with respect to their age and gender. The study utilized a web-based questionnaire distributed across 850 respondents selected from Nigeria’s petroleum industry with different job roles. A total of 550 feedbacks representing 64.71% of the total sample population for the study were received. SPSS software was first used to analyze descriptive statistics of demographic information such as age, gender, work-experience, employment type, and job category. The prevalence of stress and the level experienced by the respondents were analyzed using cross-tabulation and correlation on the questionnaires. The percentage of responses for each item used to measure the occupational stress factors in the oil and gas industry was examined in order to understand the extent to which the respondents agree or disagree with the questions. The findings showed that over 95% of the workers in petroleum industry experience stress from their jobs from a moderate level to an extreme level. 111 respondents of the 550 workers surveyed indicated that their jobs were very stressful, which accounted for 20.2% of the total respondents. 45.8% of the respondents said their jobs were moderately stressful, 31.8% were mildly stressful while 2.2% of respondents said their job were not stressful at all. it can be observed that 39.1% of workers between the ages of 20-29 years complained that their job was very stressful, 31.1% of the workers between the ages of 30-39 years complained that their jobs were very stressful, 11.5% of worker between the ages of 40-49 years complained that their jobs were very stressful and none of the worker above the age of 50 years complained that their jobs were very stressful. The survey also showed that 22.1% of male workers indicated that their jobs were very stressful while 9.6% of female workers indicated that their jobs were very stressful. This study has shown that workers of all ages in the oil and gas industry experience different levels of stress and greater number of male workers are more distressed at work than their female counterparts. Further study is needed with equal number of male and female participants in similar jobs roles with the same age groups. This will provide more details that could be used to develop specific stress management models with respect to the age and gender of oil and gas industry workers in Nigeria.